Optimising Tropical Group Bali's Food Processing Business Process using a Web-Based Information System - Sumesta, I Gede Adhipramana Putra; Satyawan, I Wayan Wahyu Gedas Adi (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
The food ordering information system serves as a viable solution for managing the food ordering procedure within the firm. The company faces challenges in its food ordering process, which is currently conducted manually using paper notes. This manual approach leads to errors, particularly during busy periods at the restaurant. These errors include the accumulation of notes, unsorted orders, and incorrect deliveries. As a result, employees are required to exert more effort and concentration to address these issues. The system design commences with the initial step of scrutinizing the accumulated data. Moreover, the design phase, also known as system design, employs a systematic approach that begins with the creation of an Event List, Use Case Diagram, and User Interface. Subsequently, the system is designed and tested using the black box testing method.